Currency Demand, the Underground Economy, and, Tax Evasion-The Case of Guyana - Faal, Ebrima (IMF Working Papers; Working Paper ;, 2003)
The persistence in Guyana of a substantial underground economy is an important consequence of economic and social policy over 1964-2000. The paper attempts to estimate the magnitude of, and changes to the underground economy in Guyana, as well as its adverse effect on tax collection, during this period.